2021
DOI: 10.1002/rmb2.12417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of intrauterine infusion of platelet‐rich plasma in patients with recurrent implantation failure

Abstract: Purpose This study aimed to evaluate the effectiveness of intrauterine infusion of platelet‐rich plasma (PRP) before embryo transfer (ET) in recurrent implantation failure (RIF) cases. Methods The authors retrospectively analyzed 54 ET cycles involving frozen and thawed high‐quality blastocysts after intrauterine PRP infusion between September 2019 and November 2020. All patients had a history of at least two times of implantation failure on ET. A total of 54 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…According to the results of the blastocyst-stage embryos (BSE)/cleavage-stage embryos (CSEs) transfer, further analysis of the data revealed that statistical differences in the β-hCGpositive rate, CPR, and LBR were only found between the BSE, PRP, and BSE control groups, which is similar to observations in other studies [29,30], whereas the three variables were similar in the CSE, PRP, and CSE control groups. This is a different result from that obtained for women with a history of RIF, whereby the PRP treatment appeared to improve the FET outcomes, with an increase in CPR and LBR [22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…According to the results of the blastocyst-stage embryos (BSE)/cleavage-stage embryos (CSEs) transfer, further analysis of the data revealed that statistical differences in the β-hCGpositive rate, CPR, and LBR were only found between the BSE, PRP, and BSE control groups, which is similar to observations in other studies [29,30], whereas the three variables were similar in the CSE, PRP, and CSE control groups. This is a different result from that obtained for women with a history of RIF, whereby the PRP treatment appeared to improve the FET outcomes, with an increase in CPR and LBR [22].…”
Section: Discussionsupporting
confidence: 81%
“…To our knowledge, research on the efficacy of PRP intrauterine infusion for patients with RIF is ongoing. Positive results have been reported in several studies [29][30][31]. However, a few studies did not show a significant improvement with the PRP treatment [18], which could be related to differences in PRP preparation and administration techniques.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to its release of all the growth factors in PLTs, PRP can also induce the overexpression of endogenous growth factors. Moreover, the high‐density granules in PLTs contain a large quantity of cytokines, chemokines, and active proteins, which participate in the regulation of inflammatory response and are an important stage of tissue repair 37 . This study also confirms that the patient's PLT level before PRP collection is one of the independent risk factors affecting the primary healing results, and the non‐primary healing rate decreases by 0.8% for every unit of increase in PLT.…”
Section: Discussionsupporting
confidence: 74%
“…All the studies were single centers except Kusumi [ 35 ], which was conducted in 7 fertility clinics. Eleven studies were conducted in Iran, 3 in Russia [ 22 , 29 , 34 ], 3 in China [ 17 , 36 , 39 ], 2 in India [ 38 , 45 ], 2 in Japan [ 35 , 41 ], and 1 study was conducted in each of the following countries: Bahrain [ 28 ], Canada [ 40 ], Egypt [ 20 ], South Korea [ 37 ], Turkey [ 42 ], and UK [ 32 ]. In 12 studies, the participants had recurrent implantation failure, in 5 studies had implantation failure, and in 10 studies, had thin endometrium.…”
Section: Resultsmentioning
confidence: 99%